Analisis kinerja pada perawat RSUD Tipe C di Propinsi Riau - Yapentra, Arhipen (Jurnal Daya Saing, 2015)
Abstrak: The purpose of this study was to determine the effect of leadership on nurse motivation, the influence of organizational culture on nurse work motivation, Influence of leadership on nurse performance, the influence of organizational culture on the performance of nurse and The influence of motivation on the nurses performance on RSUD type C in the province of Riau. Type of research was selected is quantitative survey approach. The data used is primary data that collected from 79 nurses at two hospitals from two counties. Secondary data obtained from the author profile data Riau Health Service and source data from both hospitals. Data were analyzed using path analysis technique (Path Analysis). Based on the results of the study concluded that: 1) Leadership is not a significant effect on the motivation of nurses working with the calculation of a score of 0.154. and sig 0,104 2) Cultural organizations have a significant effect on the motivation of nurses working at 0.665 and sig 0,000. 3) Leadership is significant effect on the performance of nurses at 0,265 and sig 0,008 4) Cultural organizations have a significant effect on the performance of Nurses at 0.329 and sig 0,009. 5) Motivation significant effect on the performance of Nurses at 0,273. 6) Indirect effect X1 on Y through X3 for ρx3x1. ρyx3 = (0.154). (0.273) = 0.042. So that the total effect of X1 on Y through X3 is equal to 0.042, and 7) Indirect effect X2 on Y through X3 for ρx3x2. ρyx3 = (0.665). (0.237) = 0.182. Total effect on Y through X3 X2 is equal to 0.182 Keywords : Performance, Leadership, Organizational Culture, andWork Motivation